Degradation of Methylene Blue Using Sodalite from Natural Clay Impregnated Fe - Firdaus Malik (LPPM, Institut Teknologi Sepuluh Nopember, 2020)
The purpose of this study was to utilize the potential of natural clay in the Riau, synthesized into sodalite to degrade methylene blue dye. Synthesis of natural clay sodalite has been carried out using the reflux method. The clay was leached using 3 M H2SO4 for 3 hours, calcination at 750oC for 3 hours, then aging with 5 M NaOH for 7 hours at 80 oC with a magnetic stirrer stirring and refluxed for 8 hours at 100oC, then impregnated using FeCl3.6H2O and calcined at 300oC for 4 hours. Based on the diffractogram the formation of sodalite is indicated by a peak 2θ = 14.117°; 19.743°; 24.598°; 31.927° dan 35.082°. The results of the sodalite micrograph are spherical irregular, Based on the results of the degradation process of methylene blue by sodalite/Fe-clay Maredan and the highest percentage of methylene blue decolorization was 99.98%.